Intravital imaging technology guides FAK-mediated priming in pancreatic cancer precision medicine according to Merlin status - Murphy, Kendelle J.; Reed, Daniel A.; Vennin, Claire; Conway, James R. W.; Nobis, Max; Yin, Julia X.; Chambers, Cecilia R.; Pereira, Brooke A.; Lee, Victoria; Filipe, Elysse C.; Trpceski, Michael; Ritchie, Shona; et al. (Science advances, 2021)
Intravital imaging guides a personalized medicine approach to target mechanoreciprocity in pancreatic cancer. Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic, chemoresistant malignancy and is characterized by a dense, desmoplastic stroma that modulates PDAC progression. Here, we visualized transient manipulation of focal adhesion kinase (FAK), which integrates bidirectional cell-environment signaling, using intravital fluorescence lifetime imaging microscopy of the FAK-based Förster resonance energy transfer biosensor in mouse and patient-derived PDAC models. Parallel real-time quantification of the FUCCI cell cycle reporter guided us to improve PDAC response to standard-of-care chemotherapy at primary and secondary sites. Critically, micropatterned pillar plates and stiffness-tunable matrices were used to pinpoint the contribution of environmental cues to chemosensitization, while fluid flow–induced shear stress assessment, patient-derived matrices, and personalized in vivo models allowed us to deconstruct how FAK inhibition can reduce PDAC spread. Last, stratification of PDAC patient samples via Merlin status revealed a patient subset with poor prognosis that are likely to respond to FAK priming before chemotherapy.